Wellness and job involvement among Malaysia counsellors - Ng, Haw Kuen; Wan Jaafar, Wan Marzuki (Malaysia Association of Research and Education for Educators, 2017)
The purpose of this study is to determine the relationship and influence between wellness and job involvement among counsellors in Malaysia. Correlation research design was used in this study. 340 respondents from the schools in Malaysia were chosen through stratified sampling. The instruments used in this study are The Five Factor Wellness Inventory (5F-WEL) and Kanungo Job Involvement inventory, which aim to measure the level of wellness and job involvement respectively. The Cronbach’s Alpha Coefficients for the 5F-WEL is .94 and Job Involvement is .85. Data were analyzed using Pearson correlation and Multiple Linear Regression. The results showed a significant positive relationship between wellness and job involvement (r = .227). The Multiple regression analysis also showed wellness being the significant predictor towards job involvement (R2= .086, F (5, 334) = 6258, p< .05). The Creativity Self (β = .253, t= 3381, p< .05) had significant regression weights, indicating Creativity Self has a stronger influence on job involvement compared to other wellness factors. However, mean score comparison between 5F-WEL (M=81.72) and counsellors (M=78.28, we found that our counsellors still have to improve their on wellness. In addition, the study also found that respondents had a high level of job involvement and below mean score of wellness. Overall, the findings of this study provide significant implications and guidelines on the wellness and job involvement for counselling practitioners in Malaysia.